Optimal prandial timing of bolus insulin in diabetes management: a review. Issue 3 (6th November 2017) - Slattery, D.; Amiel, S. A.; Choudhary, P.
Abstract: The inability to achieve optimal diabetes glucose control in people with diabetes is multifactorial, but one contributor may be inadequate control of postprandial glucose. In patients treated with multiple daily injections of insulin, both the dose and timing of meal‐related rapid‐acting insulin are key factors in this. There are conflicting opinions and evidence on the optimal time to administer mealtime insulin. We performed a comprehensive literature search to review the published data, focusing on the use of rapid‐acting insulin analogues in patients with Type 1 diabetes. Pharmacokinetic and pharmacodynamic studies of rapid‐acting insulin analogues, together with postprandial glucose excursion data, suggest that administering these 15–20 min before food would provide optimal postprandial glucose control. Data from clinical studies involving people with Type 1 diabetes receiving structured meals and rapid‐acting insulin analogues support this, showing a reduction in post‐meal glucose levels of ~30% and less hypoglycaemia when meal insulin was taken 15–20 min before a meal compared with immediately before the meal. Importantly, there was also a greater risk of postprandial hypoglycaemia when patients took rapid‐acting analogues after eating compared with before eating. What's new?: Taking rapid‐acting insulin 15–20 min before a meal provides significant improvements in post‐meal control; we recommend this whenever safely possible. People with diabetes who routinely bolus pre‐meal have better HbA1c values, according to large registry data. Post‐meal bolusing may increase the risk of hypoglycaemia. Advice about timing of bolus needs to be tailored in some special circumstances (e.g. pregnancy, emergency work, gastroparesis).